The Role and Importance of Risk Factors in the Development of Laryngeal Cancer During the COVID-19 Pandemic - Gnjatić, Mirjana; Vranješ, Dalibor; Jurišić, Branko; Nežić, Vanja (Scripta Medica, 2024)
Background/Aim: Laryngeal cancer is one of the most common malignancies in the head and neck region, with the highest incidence among 50 years old patients. The leading risk factors are alcohol consumption and tobacco use as the most correlated behaviours. This study aimed to assess the extent of laryngeal cancer and leading risk factors for the onset of the disease during the COVID-19 pandemic.Methods: This retrospective study included 102 patients who were treated both diagnostically and therapeutically for laryngeal cancer during a 1-year period. All patients had a previous history of being treated for COVID-19.Results: The sample included male (88.3 %) and female (11.7 %) respondents. The age group 60-69 years was predominant (40.0 %). The youngest patient was 41 and the oldest 82. Total laryngectomy was performed in 15.7 % of patients, while partial laryngectomy was performed in 57.85 % patients. Advanced stages of the cancer (T3, T4) prevented 17.65 % patients from receiving surgery. Tobacco use was the most leading risk factor (99 %).Conclusion: Advanced stages (T3, T4) of laryngeal cancer and radical surgical techniques with a potentially high rate of disability showed a higher incidence during the COVID-19 pandemic. The COVID-19 pandemic impacted timely diagnosis and delays between diagnosis and surgical treatment of the cancer. Old age, male gender and tobacco use proved to be the most common risk factors of laryngeal cancer.
Keywords: Laryngeal cancer; Risk factors; COVID-19